Improving the Ability to Read and Understand Tunjuk Ajar Melayu by Tenas Effendy - Yulantomo, Aris; Azmul Fauzi, Rian; Afriadi, Deni (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2024)
Abstract The implementation of community service activities aims to increase students' insight into the ability to read and understand tunjuk ajar melayu by Tenas Effendy. Participants in this activity are students in grades X and XI of SMA Negeri 16 Pekanbaru. During the activity, students are given an introduction and recognition of the figure of Tenas Effendy and his works. The process of implementing this activity goes through several stages, at the beginning students are given a questionnaire. Furthermore, in the main stage, students are given training to sing tunjuk ajar melayu. The final result of this activity is expected to provide an increase in students' ability to understand and read tunjuk ajar melayu as a step to preserve Malay culture. In addition, these findings are expected to provide a basis for organizing similar activities in the future to develop poetry reading skills and introduce and preserve Malay culture in students.